Burr conspiracy collection
Chiefly letters to Thomas Jefferson and James Madison relating to Aaron Burr's conspiracy, trial, and acquittal, including his involvement with Harman Blennerhassett and James Wilkinson. Includes printed matter and some material in cipher. Correspondents include Erick Bollmann, William C. C. Claiborne, William Eaton, Comfort Tyler, James Wilkinson, and James Wilson.
Microfilm edition available
Microfilm produced from originals in the Manuscript Divison.
Collection material in English.
Keywords: Blennerhassett, Harman, -- 1765-1831.; Bollmann, Erick, -- 1769-1821 -- Correspondence; Burr, Aaron, -- 1756-1836.; Claiborne, William C. C. -- 1775-1817 -- Correspondence; Eaton, William, -- 1764-1811 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Tyler, Comfort, -- 1764-1827 -- Correspondence; Wilkinson, James, -- 1757-1825.; Wilson, James, -- 1742-1798 -- Correspondence; Burr Conspiracy, 1805-1807.; Ciphers; Trials (Conspiracy)